Characterization of the Tumor Immune Microenvironment in Lung Squamous Cell Carcinoma Using Imaging Mass Cytometry - Li, Ran; Lin, Ying; Wang, Yu; Wang, Shaoyuan; Yang, Yang; Mu, Xinlin; Chen, Yusheng; Gao, Zhancheng (Frontiers in Oncology, 2021)
Background: Lung squamous cell carcinoma (LUSC) is a major subtype of non-small cell lung cancer. The tumor immune microenvironment (TIME) affects the anti-tumor immune response and the patient’s prognosis, although the TIME in LUSC patients is incompletely understood. Methods: We retrospectively collected surgical specimens from patients with previously untreated primary LUSC. Histopathological examination was used to identify tumor regions and adjacent regions, and imaging mass cytometry was used to characterize the immune cells in those regions. The results were compared between regions and between patients. Results: We identified heterogeneity in the TIME when we compared different patients with LUSC, although the tumor region and adjacent region both exhibited an immune response to the tumor. The TIME typically included a large number of infiltrating and activated T-cells, especially CD8+ T-cells, which closely interacted with the tumor cells in the tumor region. There was limited infiltration of B-cells, NK cells, and NKT cells, while the major immune suppressor cells were CD33+ myeloid-derived cells. We also identified a novel population of CD3-CD4+ cells with high expression of Foxp3 and TNFα, which might modulate the tumor microenvironment and play an anti-tumor role in the TIME. Conclusions: The TIME of LUSC appears to be immunogenic and heterogenous, with predominant infiltration of activated CD8+ T-cells. The interactions between the tumor cells and T-cells facilitate the anti-tumor activity. A novel subpopulation of CD3-CD4+ cells with high TNFα and Foxp3 expression may modulate the tumor microenvironment and play an anti-tumor role.